2019
DOI: 10.1590/0004-282x20190103
|View full text |Cite
|
Sign up to set email alerts
|

Use of client-centered virtual reality in rehabilitation after stroke: a feasibility study

Abstract: Patient-centered virtual reality (VR) programs could assist in the functional recovery of people after a stroke. Objectives: To analyze the feasibility of a rehabilitation protocol using client-centered VR and to evaluate changes in occupational performance and social participation. Methods: This was a mixed methods study. Ten subacute and chronic stroke patients participated in the rehabilitation program using games in non-immersive VR for 40 minutes/day, three days/week, for 12 weeks. Sociodemographic info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 29 publications
4
25
0
Order By: Relevance
“…[40] In our study, positive changes in the score of occupational performance were observed in both groups; the score was 2 points greater than the baseline, indicating a clinically signi cant improvement in occupational performance, and no between-group difference was found. The result of our study was consistent with those of current studies, [25,41] although the number of VR-related studies using occupational performance as an outcome indicator is insu cient. Furthermore, it was reported that a patient-centered treatment enables therapists to fully consider each patient's satisfaction, desire, and goals, which in turn makes the promotion of enthusiasm among participants easier, thereby resulting in adherence to intervention and patient satisfaction.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…[40] In our study, positive changes in the score of occupational performance were observed in both groups; the score was 2 points greater than the baseline, indicating a clinically signi cant improvement in occupational performance, and no between-group difference was found. The result of our study was consistent with those of current studies, [25,41] although the number of VR-related studies using occupational performance as an outcome indicator is insu cient. Furthermore, it was reported that a patient-centered treatment enables therapists to fully consider each patient's satisfaction, desire, and goals, which in turn makes the promotion of enthusiasm among participants easier, thereby resulting in adherence to intervention and patient satisfaction.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, it was reported that a patient-centered treatment enables therapists to fully consider each patient's satisfaction, desire, and goals, which in turn makes the promotion of enthusiasm among participants easier, thereby resulting in adherence to intervention and patient satisfaction. [25] However, the VR training in our study was not designed for target therapeutic activities. The movements in the VR games were designed in a single direction; thus, the VR group could not transform the therapeutic activity to complex daily activities during training.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations